Barreiras fitossanitárias sobre as importaç\~oes no Brasil: O caso da aveia - Uallace Moreira Lima (Instituto de Pesquisa Econômica Aplicada (IPEA), 2019)
– The main of that paper is to analyze the evolution of oat production in Brazil and its relation with its foreign trade, especially considering the possible impacts that non-tariff barriers may have on the dynamics of oats imports by the brazilian economy. For that, in addition to considering the oat databases in the world and in Brazil, the UNCTAD model of collection, registration and categorization is used as the mechanism of analysis, which is one of the main sources of non-tariff data in the world, namely UNCTAD's Trade Analysis and Information System (TRAINS). From the information researched in these databases, we adopted the partial equilibrium model with constant elasticity of Armington (EP-CES) and the estimation of equivalent tariff that follows the price-wedge method. The results showed that the economic opening through elimination of the tariff greatly affects the domestic market of oats in Brazil.
Keywords: F10; F13; Q17; 330; oats; non-tariff barriers; equivalent tariff